2017
DOI: 10.5430/ijfr.v8n2p124
|View full text |Cite
|
Sign up to set email alerts
|

Fair Value Information, Audit fees and Audit Committee in Taiwan

Abstract: Regulatory requirements to adopt IFRS and to disclose audit fees make it possible to examine association between audit fees and proportion of fair-valued assets among firms in Taiwan. A voluntary choice of adding audit committee in the firm for monitoring purpose also helps to examine the association further. Empirical results indicate that lower audit fees is related to higher proportion of (Level 2) fair-valued assets, a finding consistent to Goncharov et al.'s (2014) suggestion that firms pay lower audit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, the study found a difference in the non-current assets' fair value on audit fees through corporate governance represented by the independent board of directors as well as a difference in the non-current assets' fair value on audit fees by different fair value valuation methods measured at the first, second and third levels. Barth and Landsman, 2010;Laux and Leuz, 2009;Landsman, 2007;Wu et al, 2017 al., 2014;Hapsari and Apandi, 2018;Goncharov et al, 2014;Shamsaddini and Amiri, 2017;Wu et al, 2017…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study found a difference in the non-current assets' fair value on audit fees through corporate governance represented by the independent board of directors as well as a difference in the non-current assets' fair value on audit fees by different fair value valuation methods measured at the first, second and third levels. Barth and Landsman, 2010;Laux and Leuz, 2009;Landsman, 2007;Wu et al, 2017 al., 2014;Hapsari and Apandi, 2018;Goncharov et al, 2014;Shamsaddini and Amiri, 2017;Wu et al, 2017…”
Section: Introductionmentioning
confidence: 99%